Radikalisasi Pluralisme sebagai Usaha Pengarusutamaan Politik Agonistik - Ignasius Jaques Juru (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2010)
Current political space with its variety on identities has resulted on the difference to the political interests. This situation requires the rethinking of new form of political pluralism. Moreover, the idea to rethinking new form of political pluralism has been raised, there is radicalization of pluralism through agonistic politics. This idea need to be flourished in order to create democratization in society. This article discusses how political activities among the plurality of political identities. Relations constructed based on the relation of politics where the antagonism is present as a political necessity.